IPadPix—A novel educational tool to visualise radioactivity measured by a hybrid pixel detector. (23rd November 2016) - Keller, O.; Schmeling, S.; Müller, A.; Benoit, M.
Abstract: With the ability to attribute signatures of ionising radiation to certain particle types, pixel detectors offer a unique advantage over the traditional use of Geiger-Müller tubes also in educational settings. We demonstrate in this work how a Timepix readout chip combined with a standard 300μm pixelated silicon sensor can be used to visualise radioactivity in real-time and by means of augmented reality. The chip family is the result of technology transfer from High Energy Physics at CERN and facilitated by the Medipix Collaboration. This article summarises the development of a prototype based on an iPad mini and open source software detailed in ref. [1]. Appropriate experimental activities that explore natural radioactivity and everyday objects are given to demonstrate the use of this new tool in educational settings.